La suspensión del régimen de visitas y su incidencia frente al derecho constitucional del menor al entorno familiar, en los trámites de la unidad judicial de la Familia, Mujer, Niñez y Adolescencia del cantón Riobamba, en el año 2015 - Falconí, Robert (2017)
The visits are considered to be a right that parents and children have to strengthen family ties, while the minor's constitutional right to the family is the guarantee that minors have the right to share with their parents and to benefit from their care, which improves their development. However, when a measure of protection has been decreed in favor of the son or daughter due to physical, psychological or sexual violence, the judge may deny visitation to the aggressor parent or regulate visits in a targeted manner, depending on the severity of violence. The present investigation determines that the suspension of the right to visits, established in the second paragraph of art. 122 of the Organic Code of Childhood and Adolescence in force preponderate before the constitutional right that the child has to develop in a family atmosphere of affection and security. For what was analyzed the jurisprudence and doctrine in the matter, in addition interviews and surveys were carried out directed to lawyers in free exercise and judges of the Family Unit of the City of Riobamba. From the investigation carried out, it is concluded that the suspension of the visitation system guarantees and warrants the physical and emotional integrity of the child or adolescent, according to the principle of the best interests and their rights prevail over that of other persons.